The activities in the west in the 1950s to free Lithuania: the supreme committee for the liberation of Lithuania in 1944-1950 - Banionis, Juozas (Genocidas ir rezistencija, 2007)
• Reestablished in West Germany on 8 April 1945, the Vyriausiasis Lietuvos iglaisvinimo komitetas (VLIK, the Supreme Committee for the Liberation of Lithuania), which was originally an anti-Nazi organisation, became anti-Soviet. It consisted of political parties in the Seimas in Lithuania and resistance movements formed in occupied Lithuania, with two blocs: Christian and anticlerical. The VLIK made changes to the 16 February 1944 Declaration and published the Wiirzburg Protocol on 3 July 1945. According to this, the political system in liberated Lithuania was to be created on the basis of the 1922 Constitution. In the guidelines for its liberation, which were based on the principles of the Atlantic Charter, much hope was placed on the pending Peace Conference. • Between 1944 and 1950, one of the most important aims of the VLIK was to organise a Lithuanian government in exile (originally an executive body performing the functions of a government). To this aim, relations with the Lithuanian Diplomatic Service (LDT) were to be regulated. Meetings between the two institutions were held. Following the 21-26 July 1946 meeting in Bern, an Executive Council (VT), a political body with government functions, was formed. • The Executive Council formed on 12 October 1946 did not perform any functions. In 1947, following the resignation of its chairman and the head of the foreign service, a new council was formed. It participated successfully in the sphere of Lithuania’s liberation. At the Paris meeting on 5-15 August 1947, the issue of Lithuania’s liberation and the continuing armed resistance in the occupied country were discussed widely. The role of the VLIK and the Executive Council in the liberation process was marked, although an agreement between the two institutions was not reached. A decision to seek “closer and more perfect cooperation” was reached. • Promoting the case for the liberation of Lithuania in the West and striving to form a government in exile, the VLIK worked out and sent memoranda and statements to the leaders of the USA, Great Britain and other large countries. The documents stressed the hopes for the freedom of the Lithuanians, expressing at the same time concern about the situation in the occupied country, i.e., the armed resistance, mass deportations, and the fate of refugees in the West. • In the second half of the 1940s, on the initiative of the VLIK and with the approval of the ALT, the issue of organising political deportees came to the fore. On 3 March 1946, a Community of Lithuanian Deportees was established in Hanau, with the functions of upholding the national identity and education. Shortly afterwards, at a political conference of Lithuanian deportees, it was noted that the Community of Lithuanian Deportees should join the liberation activities and it had to “get ready for rebuilding Lithuania”. Before political refugees scattered all over the free world, the Lithuanian Charter was published on 14 June 1949. This document laid an ideological basis for patriotically minded Lithuanian émigrés, and provided premises for the formation of Lithuanian communities in different countries in the 1950s, which later united into the World Lithuanian Community.